Factors signifying gender differences in clinical presentation of sarcoidosis among Estonian population. (29th September 2014) - Lill, Hille; Kliiman, Kai; Altraja, Alan
Abstract: Introduction: Sarcoidosis is endemically prevalent in Northern Europe, but gender differences among the sarcoidosis population have not yet been compositely addressed. Objectives: To reveal independent factors that formulate gender differences in the presentation of sarcoidosis. Methods: All Caucasian patients with confirmed sarcoidosis were recruited from the outpatient department of the Lung Clinic of the Tartu University Hospital, Estonia, between February 2009 and April 2011. Data on demographics, complaints, symptoms, clinical presentation, extrapulmonary manifestations, radiographic stage, lung function parameters and sarcoidosis‐related laboratory indices were all drawn from patients' clinical records at presentation. Factors characteristic of female gender were estimated using multivariate logistic regression analysis. Results: Of 230 cases included, there were significantly more females (56.5%, P = 0.005). After adjustment for age, females appeared distinguishable from males by older age [adjusted odds ratio (OR) 1.04, 95% confidence interval (CI) 1.02–1.07], less frequent smoking (OR 0.25, 95% CI 0.13–0.49), higher probability of extrapulmonary complaints (OR 2.06, 95% CI 1.16–3.65) and musculoskeletal sarcoidosis (OR 3.22, 95% CI 1.65–6.29), and after adjustment for both age and smoking status lower forced expiratory volume in 1 s and lung carbon monoxide diffusing coefficient % predicted (OR 0.89, 95% CI 0.82–0.97 and OR 0.98, 95% CI 0.96–0.995, respectively), but by higher forced vital capacity % predicted (OR 1.12, 95% CI 1.03–1.22). Conclusion: Women with sarcoidosis are independently characterized by greater airflow obstruction, lower lung diffusing coefficient, older age, less smoking, and more frequent extrapulmonary complaints and musculoskeletal involvement. This may urge special attention when addressing female patients in both differential diagnostic and management settings.